Conotoxin-derived biomimetic coiled cone-shaped peptide as ligand for selective nanodelivery to norepinephrine transporter-expressing neuroblastoma cells. (June 2022) - Zivotska, Hana; Mokry, Michal; Rodrigo, Miguel Angel Merlos; Michalkova, Hana; Kapolkova, Katerina; Splichal, Zbynek; Stokowa-Soltys, Kamila; Milosavljevic, Vedran; Guran, Roman; Richtera, Lukas; Haddad, Yazan; Rex, Simona; et al.
Highlights: Conotoxin-derived peptides were designed in silico and synthesized. Peptides were immobilized onto ferritin delivery vehicles loaded with ellipticine. Use of peptides led to selective cytotoxicity against hNET expressing cells. YKL-6 peptide markedly improved anticancer activity of ellipticine in vivo . Abstract: Selective drug delivery is an emerging powerful strategy, which promises efficient and safer neuroblastoma treatment in contrast to conventional therapeutic modalities. Herein, we present a newly designed apoferritin nanovehicle loaded with ellipticine and decorated with conotoxin-derived biomimetic peptide YKL-6 (sequence: YKLYKLYKLYKLYKLYKLC) to target the norepinephrine transporter (hNET), which is highly expressed on neuroblastoma cells membrane. The peptide forms a coiled cone-shape forming anti-parallel beta sheets in aggregation in vitro . Molecular docking analysis suggests electrostatic interaction mediated by lysine residues against negatively charged residues of the hNET. The assembled nanovehicles show optimal biocompatibility in healthy epithelial cells and ability to deliver ellipticine into neuroblastoma cells (UKF-NB-4 and SH-SY5Y). In our analyses, we have excluded hNET-mediated endocytosis as an uptake mechanism and demonstrated the ellipticine-triggered anti-proliferative mechanisms in neuroblastoma cells via downregulation of Bcl-2, survivin and N-myc. Finally, we present a selective inhibition of neuroblastoma growth and metastasis in vivo in an ex ovo and in ovo chicken chorioallantoic membrane assay. Overall, these findings demonstrate a great leap forward in the design of biomimetic homing peptides towards possible application in neuroblastoma nanomedicine. Graphical abstract: Image, graphical abstract